The Design and Application of Controlled Low-Strength Materials (Flowable Fill) 1998
DOI: 10.1520/stp13066s
|View full text |Cite
|
Sign up to set email alerts
|

Admixture Enhanced Controlled Low-Strength Material for Direct Underwater Injection With Minimal Cross-Contamination

Abstract: Commercially available admixtures have been developed for placing traditional concrete products under water. This paper evaluates adapting anti-washout admixture (AWA) and high range water reducing admixture (HRWFL4) products to enhance controlled low-strength materials (CLSMs) for underwater placement. A simple experimental scale model (based on dynamic and geometric similitude) of typical grout pump emplacement equipment has been developed to determine the percentage of cementing material washed out. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Utilizing wash out resistant CLSM can enhance CLSM for underwater placement (Hepworth et al, 1998). The wash out resistant CLSM can be used as a stabilizing agent for the remediation tanks of contaminated materials.…”
Section: Controlled Low Strength Materials (Clsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing wash out resistant CLSM can enhance CLSM for underwater placement (Hepworth et al, 1998). The wash out resistant CLSM can be used as a stabilizing agent for the remediation tanks of contaminated materials.…”
Section: Controlled Low Strength Materials (Clsm)mentioning
confidence: 99%
“…The wash out resistant CLSM can be used as a stabilizing agent for the remediation tanks of contaminated materials. Hepworth, et al (1998) concluded that admixture-enhanced CLSM helps minimize the washout contamination of tank fluid and cross-contamination of the CLSM.…”
Section: Controlled Low Strength Materials (Clsm)mentioning
confidence: 99%